Cellular Immunotherapy and Locoregional Administration of CAR T-Cells in Malignant Pleural Mesothelioma - Belderbos, Robert A.; Vroman, Heleen; Aerts, Joachim G. J. V. (Frontiers in Oncology, 2020)
Malignant pleural mesothelioma (MPM) is a lethal treatment resistant tumor with a poor prognosis from diagnosis. Overall survival after first line combination chemotherapy is 9-12 months. No second line treatment has been registered. Current treatment options, such as Checkpoint Inhibitors (CI) and targeted therapy, that are flourishing in non-small cell lung cancer (NSCLC), have not yet proven to be effective in MPM. CIs have shown promising results for MPM in phase I/II trials, but not in a randomized phase III trial. MPM is a cold tumor with low T-cell infiltration. As CIs reinvigorate T-cells, it is hypothesized that the lack of efficacy of CI treatment in MPM is due to the low number of tumor infiltrating T-cells. Induction of an anti- tumor immune response through cellular therapies and cancer vaccines can lead to an increase of the number of TILs. In this review we will evaluate currently used cellular therapies and vaccines, such as cancer vaccines, DC therapy and CAR-T cell therapy used for treating MPM.